Umur, Interval Kehamilan, Kehamilan yang Diinginkan dan Perilaku Pemeriksaan Kehamilan - Retno Dumilah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2019)
Antenatal care (ANC) is an effort to supervision a pregnant woman in order to be ready physically or mentally to serving pregnancy, childbirth and postpartum. Comprehensive and regularly antenatal care can detection abnormality and risk early that might arise during pregnancy, so that it can be correction quickly and correctly. Although the coverage of antenatal care in Karawang Distric is 100%, but the coverage of Rawamerta Health Center only 75.25%. The aim of this study was to determine the correlation between maternal ages, pregnancy interval and intended pregnancy with regularly antenatal care practice at Rawamerta Health Center, Karawang District. Cross sectional research was conducted in February to October 2018. The source of the data was the note of antenatal care (i.e MCH) and questionnaires, covering of 41 multiparous intrapartum women was chosen by purposive sampling. Statistical analysis was performed with Chi Square test. The results shown that there’s no significant correlation between maternal ages and pregnancy interval with regularly antenatal care practice. But intended pregnancy increasing regularly antenatal care practice up to 5.1 times at Puskesmas Rawamerta, Karawang District (p